Identifikasi bakteri Escherichia coli dan Salmonella sp. pada Spons Pencuci Piring Berdasarkan Lama Penggunaan - Turrohmah, Alhidayah; Khusna, Umi Nihayatul; Jaman , Anwar (Asosiasi Institusi Pendidikan Tinggi Teknologi Laboratorium Medik Indonesia, 2025)
Background: Sponges are tools used to clean cutlery. Dishwashing sponges are the main source of bacterial cross-contamination because they can transmit foodborne pathogens. Sponges that are used for a long time will have more potential to grow various microorganisms, such as bacteria from the Enterobacteriaceae family, including Escherichia coli and Salmonella sp. Objectives: The purpose of this study was to identify Escherichia coli, Salmonella sp..and the proper duration of use on sponges to avoid bacterial contamination. Materials and Methods: The type of research is descriptive, with a Quota sampling technique with a sample size of 6 dishwashing sponges at 6 points in the house (2 samples at one time), which have been determined on three indicators, namely 3,5,7 weeks of use. Observation and testing data collection methods. Results: The results showed negative Esherichia coli bacteria in all sponge samples with a duration of use of 3, 5, and 7 weeks, while positive Salmonella sp. bacteria in 1 sponge sample with a duration of use of 7 weeks. Conclusions: There were Salmonella sp. bacteria in 1 sample, namely a sponge used for 7 weeks and no Escherichia coli bacteria were found in all samples, all samples of dishwashing sponges with a usage period of 3, 5, and 7 weeks tested positive for bacterial contamination, so the minimum usage period for the sponge is 2 weeks, to avoid bacterial contamination from the dishwashing sponge.